Modification of deproteinised natural rubber by graft-copolymerisation of methyl methacrylate - Yusof Nurul HayatiKawahara Seiichi; Mazam Md Said (Journal of Rubber Research, 2008)
DL
Keywords: Deproteinisation; Graft-copolymerisation; Methyl methacrylate; Sodium dodecyl sulfate (SDS); U-DPNR latex; Urea